Trame di un quartiere: Pratiche e narrazioni per ricostruire un diritto alla città - Lo Re, Vincenzo Luca (Antropologia Pubblica, 2019)
This contribution analyses the process of empowerment and collective en-gagement which is taking place in San Berillo’s neighbourhood in Catania, Sicily, as a result of the project named Trame di quartiere. Since 2015, this project has been pro-posed various social and cultural activities for involving inhabitants in the reshaping of abandoned spaces in their urban area. The project indeed aims to create new relation-ships between the “city of stone” and citizens, by definingan enabling space where cultural values, social practices and meanings produce a communitarian and incremental form of urban planning using a bottom up approach. The association Trame di quartiere connects research such as community mapping, oral history, participant observation and video documentation with action in the same manner with co-design, social aggregation in order to encourage material and immaterial space-making strategies and to strength the cooperative relationship among inhabitants. The tools and approaches used in the project are based on the idea that a public dimension of anthropology may have an effect on the neighbourhood. The cultural inheritance of local communities represents a way of regeneration in which forms of participation and empowerment respond to the needs of creating a process which leads to an individual and collective development. The activities carried out by inhabitants such as “Vai Via” and “Narrazioni di quartiere” represent a specific material and a symbolic resource for an inclusive urban project.